2022
DOI: 10.3847/1538-4357/ac5f40
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Nuclear Matter in Relativistic Mean-field Models with Isoscalar- and Isovector-meson Mixing

Abstract: Using the relativistic mean-field model with nonlinear couplings between the isoscalar and isovector mesons, we study the properties of isospin-asymmetric nuclear matter. Not only the vector mixing, ω μ ω μ ρ ν ρ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…Also in Zabari et al (2019a), the ω meson self-interactions and the crossing term ρ-ω are not considered. A similar study has been performed very recently in Miyatsu et al (2022).…”
Section: Introductionsupporting
confidence: 56%
“…Also in Zabari et al (2019a), the ω meson self-interactions and the crossing term ρ-ω are not considered. A similar study has been performed very recently in Miyatsu et al (2022).…”
Section: Introductionsupporting
confidence: 56%
“…As mentioned in the introduction, we consider various types of RMF effective interactions: LHS (Reinhard 1989), RMF201 (Dadi 2010), NL3 (Lalazissis et al 1997), Hybrid (Piekarewicz & Centelles 2009), TM2 (Sugahara & Toki 1994), NLSV1 (Sharma et al 2000), PK1 (Long et al 2004), NL3ωρ (Horowitz & Piekarewicz 2001), S271v6 (Horowitz & Piekarewicz 2002), HC (Bunta & Gmuca 2003), DD-LZ1 (Wei et al 2020), DD-ME2 (Lalazissis et al 2005), DD2 (Typel et al 2010), PKDD (Long et al 2004), OMEG (Miyatsu et al 2022), and the zero-range point coupling ones without exchanging mesons: DD-PC1 (Nikšić et al 2008), FKVW (Finelli et al 2006), PC-PK1 (Zhao et al 2010). They also cover all variants of the RMF models reviewed in Dutra et al (2014).…”
Section: The Rmf Modelmentioning
confidence: 99%
“…With the above considerations, we include the isoscalar scalar meson σ and vector mesons ρ and ω in GnEFT. Note that, it is recently found that the iso-vector scalar mesons δ (denoted as a 0 (980) in particle physics) also affects the EoS through the symmetry energy in a sizable way [49,50]. However, since we do not have any idea on how to construct an EFT for them and their structures are still under debate, we will not consider them in the present work.…”
Section: Hidden Symmetries and Hadron Resonancesmentioning
confidence: 99%